Susceptibility to e-cigarette among high school students: a study based on the ecological model of health behavior - Deng, Hui; Fang, Ling; Zhang, Lingyun; Li, Jie; Wang, Jing; Wang, Fan; Zheng, Pinpin (Frontiers in Public Health, 2024)
Introduction Youth e-cigarette (EC) use has rapidly increased in the last few years. It is crucial to identify the susceptible youth and prevent them from EC uptake. This study was conducted to investigate factors that affect youth susceptibility to EC use. Methods This study employed a cross-sectional survey design, utilizing multi-center stratified cluster sampling method to select two junior high schools and two senior high schools in Shanghai, Guangzhou, and Chengdu. One-third of classes of each grade in the selected schools were involved in this survey. After obtaining the informed consent of parents, an anonymous and self-administered questionnaire was distributed to students. Questionnaire was designed based on the Ecological Models of Health Behavior. Associations between EC susceptibility and covariates were identified using multivariate logistic regression. Results Among 2,270 students who had never vaped, 38.0% were susceptible to ECs. Logistic regression analysis identified factors on different levels affecting the susceptibility. Individual factors included senior high school students (OR = 1.34, 95% CI: 1.08–1.65), sensation seeker (OR = 1.11, 95%CI: 1.08–1.14), poor academic performance (OR = 1.24, 95% CI: 1.01–1.54), ever cigarette user (OR = 2.27, 95% CI: 1.29–4.01), unaware of the second-hand smoke from vaping (OR = 1.56, 95% CI: 1.25–1.96), agreeable with “I do not want to hang around vapers” (OR = 0.79, 95% CI: 0.64–0.97), agreeable with “ECs are more fashionable than cigarette” (OR = 2.50, 95% CI: 1.72–3.62) and favorable attitudes toward vaping (OR = 5.09, 95% CI: 3.78–6.85) were significantly associated with susceptibility to ECs. At interpersonal level, students who believe they would not be punished by parents for vaping increased susceptibility (OR = 1.27, 95% CI:1.01–1.59). At community level, exposure of EC advertising (OR = 1.81, 95% CI:1.46–2.25), exposure to hazard information (OR = 0.76, 95% CI: 0.59–0.97) and seeing vaping in daily life (OR = 2.11, 95% CI: 1.62–2.74), were statistically significantly associated with youth susceptibility to ECs. Conclusion EC susceptibility was observed in a substantial proportion of adolescents who had never vaped, influenced by factors on different levels. This research underscores the urgent need for comprehensive intervention strategies to prevent the youth susceptibility to ECs.